2010
DOI: 10.1158/0008-5472.can-09-2889
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent DR5 Peptides Activate the TRAIL Death Pathway and Exert Tumoricidal Activity

Abstract: Ongoing clinical trials are exploring anticancer approaches based on signaling by TRAIL, a ligand for the cell death receptors DR4 and DR5. In this study, we report on the selective apoptotic effects of multivalent DR5 binding peptides (TRAIL mim/DR5 ) on cancer cells in vitro and in vivo. Surface plasmon resonance revealed up to several thousand-fold increased affinities of TRAIL mim/DR5 -receptor complexes on generation of divalent and trivalent molecules, the latter of which was achieved with a conformation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 46 publications
12
88
0
6
Order By: Relevance
“…These findings are consistent with the earlier report that resveratrol induces p53-independent apoptosis in cancer cells (65,67,(73)(74)(75)(76). Although Bak can be activated by p53 (59), we did not observe p53 involvement in Bak activation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with the earlier report that resveratrol induces p53-independent apoptosis in cancer cells (65,67,(73)(74)(75)(76). Although Bak can be activated by p53 (59), we did not observe p53 involvement in Bak activation.…”
Section: Discussionsupporting
confidence: 93%
“…Because resveratrol primarily targets mitochondria to induce apoptosis, resveratrol could be used as a synergistic agent to enhance death receptor-mediated cancer cell death. Indeed, elegant works of other colleagues have demonstrated that resveratrol enhances TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis in cancer cells (67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies and clinical trials are giving promising results, supporting the potential of these combining approaches. 17,18 Cell surface expression of TRAIL agonistic receptors is the first requirement in order to trigger the TRAIL apoptotic machinery but, to date, the expression of TRAIL receptors in primary tumors remains poorly studied and the anti-apoptotic function of TRAIL-R4 remains controversial. It was found, however, in a few studies that primary lymphomas could express functional TRAIL antagonistic receptors at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to agonistic antibodies, the development of other biologic mimetics of TRAIL has been reported, this including oligomeric forms of TRAIL receptor-binding peptides (20,21) and scaffold proteins (22,23). An ideal therapeutic that activates the TRAILR2 pathway would combine the potency of the natural ligand with the favorable manufacturing attributes of antibodies.…”
Section: Introductionmentioning
confidence: 99%